South Africa's hybrid care regime: The changing and contested roles of individuals, families and the state after apartheid. (July 2018) - Button, Kirsty; Moore, Elena; Seekings, Jeremy
The post-apartheid state in South Africa inherited a care regime that historically combined liberal, social democratic and conservative features. The post-apartheid state has sought to deracialise the care regime, through extending to the African majority the privileges that hitherto had been largely confined to the white minority, and to transform it, to render it more appropriate to the needs and norms of the African majority. Deracialisation proved insufficient and transformation too limited to address inequalities in access to care. Reform also generated tensions, including between a predominant ideology that accords women and children rights as autonomous individuals, the widespread belief in kinship obligations and an enduring if less widespread conservative, patriarchal ideology. Ordinary people must navigate between the market (if they can afford it), the state and the family, balancing opportunities for independence with the claims made on and by kin. The care regime thus remains a contested hybrid.